Dual-Site Biomimetic Cu/Zn-MOF for Atopic Dermatitis Catalytic Therapy via Suppressing FcγR-Mediated Phagocytosis - Huang, Fang; Lu, Xiangyu; Kuai, Le; Ru, Yi; Jiang, Jingsi; Song, Jiankun; Chen, Si; Mao, Lijie; Li, Yongyong; Li, Bin; Dong, Haiqing; Shi, Jianlin (Journal of the American Chemical Society, 2024)
Atopic dermatitis (AD) is a prevalent chronic inflammatory skin disease that carries a significant global economic burden. Elevated levels of reactive oxygen species (ROS) have been recognized as contributing to AD exacerbation, making them a potential therapeutic target for AD treatment. Here, we introduce a dual-site biomimetic copper/zinc metal-organic framework (Cu/Zn-MOF) featuring four types of enzyme-like activities for AD treatment via suppressing the Fcγ receptor (FcγR)-mediated phagocytosis signal by mimicking the bimetallic sites of natural copper-zinc superoxide dismutase (CuZn-SOD). Interestingly, the neighboring Cu and Zn sites in both Cu/Zn-MOF and CuZn-SOD are at similar distances of ∼5.98 and ∼6.3 Å from each other, respectively, and additionally, both Cu and Zn sites are coordinated to nitrogen atoms in both structures, and the coordinating ligands to Cu and Zn are both imidazole rings. Cu/Zn-MOF exhibits remarkable SOD-like activity as well as its glutathione peroxidase (GPx)-, thiol peroxidase (TPx)-, and ascorbate peroxidase (APx)-like activities to continuously consume ROS and mitigate oxidative stress in keratinocytes. Animal experiments show that Cu/Zn-MOF outperforms halcinonide solution (a potent steroid medication) in terms of preventing mechanical injuries, reducing cutaneous water loss, and inhibiting inflammatory responses while presenting favorable biosafety. Mechanistically, Cu/Zn-MOF functions through an FcγR-mediated phagocytosis signal pathway, decreasing the continuous accumulation of ROS in AD and ultimately suppressing disease progression. These findings will provide an effective paradigm for AD therapy and contribute to the development of two-site bionics (TSB).